Transcriptomic and Proteomic Profiling of Human Mesenchymal Stem Cell Derived from Umbilical Cord in the Study of Preterm Birth. Issue 1 (9th October 2019) - Chien, Chih‐Wei; Lo, Yu‐Shu; Wu, Hsin‐Yi; Hsuan, Yogi; Lin, Chi‐Kang; Chen, Yu‐Ju; Lin, Willie; Han, Chia‐Li
Abstract : Objective: Mesenchymal stem cells (MSCs) hold great therapeutic potential in morbidities associated with preterm birth. However, the molecular expressions of MSCs in preterm birth infants are not systematically evaluated. In this study, the dual‐omics analyses of umbilical‐cord (UC)‐derived MSCs to identify the dysregulated cellular functions are presented. Materials and methods: The UC‐MSCs are collected from ten full‐term and eight preterm birth infants for microarray and iTRAQ‐based proteome profiling. Results: The integrative analysis of dual‐omics data discovered 5615 commonly identified genes/proteins of which 29 genes/proteins show consistent up‐ or downregulation in preterm birth. The Gene Ontology analysis reveals that dysregulation of mitochondrial translation and cellular response to oxidative stress are mainly enriched in 290 differential expression proteins (DEPs) while the 412 differential expression genes (DEGs) are majorly involved in single‐organism biosynthetic process, cellular response to stress, and mitotic cell cycle in preterm birth. Besides, a 13‐protein module involving CUL2 and CUL3 is identified, which plays an important role in cullin‐RING‐based ubiquitin ligase complex, as potential mechanism for preterm birth. Conclusion: The dual‐omics data not only provide new insights to the molecular mechanism but also identify panel of candidate markers associated with preterm birth.